The phylogeny, phylogeography, and diversification history of the westernmost Asian cobra (Serpentes: Elapidae: Naja oxiana) in the Trans‐Caspian region - Kazemi, Elmira (Ecol Evol, 2020)
We conducted a comprehensive analysis of the phylogenetic, phylogeographic, and demographic relationships of Caspian cobra (Naja oxiana; Eichwald, 1831) populations based on a concatenated dataset of two mtDNA genes (cyt b and ND4) across the species' range in Iran, Afghanistan, and Turkmenistan, along with other members of Asian cobras (i.e., subgenus Naja Laurenti, 1768). Our results robustly supported that the Asiatic Naja are monophyletic, as previously suggested by other studies. Furthermore, N. kaouthia and N. sagittifera were recovered as sister taxa to each other, and in turn sister clades to N. oxiana. Our results also highlighted the existence of a single major evolutionary lineage for populations of N. oxiana in the Trans‐Caspian region, suggesting a rapid expansion of this cobra from eastern to western Asia, coupled with a rapid range expansion from east of Iran toward the northeast. However, across the Iranian range of N. oxiana, subdivision of populations was not supported, and thus, a single evolutionary significant unit is proposed for inclusion in future conservation plans in this region.